Evaluating functional effects of dietary phytogenic product supplementation in Nile Tilapia through performance, immunity, gene expression, and resistance to Flavobacterium oreochromis - Ishini A Appuhami; Krishna Pada Singha; D Allen Davis; Brent M Vuglar; Fernando Y Yamamoto; Mark Farmer; Timothy J Bruce (Journal of Aquatic Animal Health, 2026)
Abstract Objective Phytogenics, which are plant-derived compounds, are increasingly gaining importance in aquaculture as sustainable and natural feed additives that support the performance and health of cultured fish. The current study evaluated the effects of dietary phytogenic supplementation in Nile Tilapia Oreochromis niloticus and the influence of phytogenics on growth, immunity, and resistance against Flavobacterium oreochromis. Methods Fish were fed six experimental diets, including a control diet and five commercial phytogenic treatments—Syrena Boost (SY), Actifor Pro, Actifor Power (APO), Enviro QS, and Fresta Protect—for 60 d in a recirculating aquaculture system. These products included bioactive compounds, such as saponins, thymol, essential oils, and condensed tannins. At the end of the trial, fish were sampled and blood was collected for serum lysozyme and biochemistry analyses, while spleen and head kidney were collected for immune gene expression analysis. After sampling, fish were challenged with F. oreochromis to evaluate resistance. Results No significant differences in growth performance or nutrient utilization were observed among dietary treatments compared with the control. However, fish that were fed with phytogenic diets exhibited enhanced innate immune responses, as indicated by increased serum lysozyme activity in the APO treatment group (mean ± SE = 17.8 ± 0.76 μg/mL) and elevated serum albumin in the SY and Actifor Pro treatment groups. Although no significant differences were found in the expression of immune-related genes (interleukin-1 beta, interleukin-6, interleukin-8, and tumor necrosis factor alpha), multivariate analysis revealed tissue-specific and diet-dependent immune patterns. During the bacterial challenge with F. oreochromis, all phytogenic treatments resulted in a significantly higher survival compared with the control group, with fish in the SY (∼58%) and APO (∼51%) treatment groups showing the lowest cumulative mortality. Conclusions These findings indicate that phytogenic compounds could enhance resistance to F. oreochromis in Nile Tilapia through modulating the innate immune response. Overall, among the five commercial phytogenics evaluated in this study, SY and APO showed the most potential as functional feed additives to improve Nile Tilapia immunity and resistance to columnaris disease.